Beyond a static documentation environment: A framework for transforming Knowledge Management Systems into user-centric service platforms - Melendez Agui, Diana Carolina; Sleibi, Lynne (My University)
In today’s dynamic business environment, effective knowledge management is critical for organizations to leverage their operational know-how. This qualitative single case study investigates the documentation environment within the Purchasing Operations Process of a global retail enterprise. Although intended to align daily operational activities with overarching strategic goals, the current system is underutilized, resulting in a disconnect between management expectations and user performance. Through empirical data and theoretical analysis, the findings reveal distinct organizational gaps. Users require practical, role-specific guidance, visual support, accessible language, and clear updates to effectively apply documented knowledge. Conversely, management needs the system to act as a structured, reliable "single source of truth" that ensures strategic alignment. The analysis demonstrates that while the documentation environment should function as a dynamic Knowledge Management System (KMS), it currently operates as a static repository where knowledge is difficult to retrieve and apply in daily routines. To resolve this, the thesis contributes a theoretical framework that reconceptualizes the documentation environment from a mere documentation repository into a user-centered service platform. This framework illustrates how both user and management needs can be seamlessly integrated to actively facilitate mutual value creation within the organization.
Keywords: Knowledge Management, Knowledge Management System, Service Management, documentation environment, knowledge transfer, user needs, management needs, service platform, value creation.